A fifth order runge-kutta RK(5,5) method with error control - Evans, D. J.; Yaakub, A. R. (Taylor & Francis, 2002)
In this paper a new Runge-Kutta RK(5, 5) method is introduced. The theory and analysis of its properties are investigated and compared with the more well known RKF(4, 5) and RK(4, 5) – Merson methods.